KONTRIBUSI TENAGA KERJA DALAM KELUARGA TERHADAP PENDAPATAN USAHATANI CABAI RAWIT (Capsicum frutescens L.) DI LANDASAN ULIN UTARAKECAMATAN LIANG ANGGANG BANJARBARU - Fitriadi, Subhan; Triatmoko, Eddy; Fenny Refiana; Melianti, Eni (Fakultas Pertanian UVAYA Banjarmasin, 2022)
The purpose of this research is to know the revenue,the eksplicit cost ,income and , feasibility. This research was conducted in September - Desember 2022 at village Landasan Ulin Utara Banjarbaru regency. The Purposive sampling methode used was by observing 11 farmers in village Landasan Ulin Utara who planted cayenne pepper plant. The Average result of the revenue is Rp. Rp82.632.727/farmer., the average Eksplicit cost is Rp. 5.435.622,20/farmer, and Average income Rp. 77.197.105,08/farmer,contribution of labours in the family 6,85%/farmer. and From this result of development of farming cayenne pepper plant.We believe that it has good prospect and revenue, of the average income ,tecnicall and economically. The contribution of labors in the family can increase farmers’ income and it should be always optimized